Efficacy of standard triple therapy versus bismuth-based quadruple therapy for eradication of Helicobacter Pylori infection - Talaie, Ramin (Archives of Advances in Biosciences, 2014)
Helicobacter Pylori is the main cause of gastric ulcer, adenocarcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma. Up to now, different regimens have been used for Helicobacter pylori (H.pylori) eradication to find the most potent and cost-effective regimen with less side effects. The aim of this study was to investigate the efficacy of standard triple therapy versus quadruple therapy for eradication of H. pylori. In a randomized clinical trial, 110 patients with H.pylori infection were randomly assigned into two groups of triple or quadruple therapy. The first group received standard triple therapy regimen with clarithromycin, amoxicillin and omeprazole and the second group received bismuth-based quadruple therapy regimen. At the end of study, stool antigen assay was used to confirm H.pylori eradication. The mean age of patients was 41.58 ± 11.98 years and 50.9% of them were male. Side effects of treatment with triple therapy were observed in 49.1% of cases. H.pylori eradication rate with triple and quadruple therapy regimen was 54.5% and 72.7% respectively but the difference was not statistically significant.Results showed that the efficacy of triple therapy was comparable to that of bismuth-based quadruple therapy regimen. However, due to the better compliance of triple therapy regimen, it is recommended for the first line treatment. Quadruple therapy could be used as an alternative treatment when triple therapy fails.